EKSISTENSI SANGGAR SARAI SARUMPUNDALAM MENGEMBANGKAN SENI TARI TRADISIONAL - Morezky, Elsa; Ayuthia Mayang Sari (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to unveil the existence of Sanggar Sarai Sarumpun in developing traditional dance. This research is qualitative with a descriptive approach. The research instruments include the researcher themselves, along with writing tools, a camera, and a flash drive. Data were collected through literature studies, observations, interviews, and documentation. The steps for data analysis include data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that Sanggar Sarai Sarumpun remains active due to its consistent efforts in creating, developing, and showcasing dances rooted in traditional Minangkabau culture into new choreographies that are adapted to contemporary developments. As a result, the performances produced have become more interesting and accessible to the younger generation as well as the wider public. The Sarai Sarumpun studio also demonstrates that success in maintaining existence is not solely determined by the quality of artistic works, but also by the social strategies employed. Through collaboration with the Government, such as the Tourism Office and the Historical Centre, along with involvement in various events with vendors, this studio has succeeded in expanding its network and opening up more opportunities. In addition to being a place for the arts, the Sarai Sarumpun studio also plays a role in the preservation of culture and the formation of character, especially for the younger generation. Support from the community, the Government, and various institutions shows that the Sarai Sarumpun studio not only survives but also thrives and has a significant impact on the preservation of culture in West Sumatra.